Hydrogen Peroxide-Induced Thymidine Incorporation Into Cultured Rat Astrocytes - Koh-ichi Tanaka; Tomoaki Sato; Yoshiko Ohnishi; Takashige Nishikawa (Elsevier, 2006)
We characterized [methyl-3H]thymidine ([3H]thymidine) and [5-3H]uridine ([3H]uridine) incorporation into cultured astrocytes and neurons in the presence and absence of hydrogen peroxide (H2O2) in order to define the response to oxidative stress in the central nervous system. [3H]Thymidine incorporation into cultured astrocytes was remarkably decreased by N6,2'-O-dibutyryladenosine 3',5'-cyclic monophosphate (DBcAMP), a permeable analogue of cAMP, which induced a morphological change from the polygonal form (undifferentiated astrocytes) to the process-bearing one (differentiated astrocytes). H2O2 induced [3H]thymidine, but not [3H]uridine, incorporation into cultured astrocytes at only an early time from 24 h after DBcAMP treatment, although the absolute quantities of [3H]thymidine incorporation into astrocytes pretreated with DBcAMP were less than those into astrocytes pretreated without DBcAMP. Hydroxyurea, a replicative DNA synthesis inhibitor, suppressed dose-dependently and completely [3H]thymidine incorporation into astrocytes pretreated without DBcAMP, but not astrocytes pretreated with DBcAMP. H2O2 did not stimulate [3H]thymidine or [3H]uridine incorporation into astrocytes pretreated without DBcAMP and neurons. These findings indicate that only astrocytes pretreated with DBcAMP are able to increase thymidine incorporation specifically in the presence of H2O2 for a purpose other than proliferation, including the repair of H2O2-induced DNA injury, for example. Keywords:: hydrogen peroxide (H2O2), thymidine incorporation, astrocyte, N6,2'-O-dibutyryladenosine 3',5'-cyclic monophosphate (DBcAMP), hydroxyurea